Severe obesity is associated with liver disease severity in pediatric non‐alcoholic fatty liver disease. Issue 2 (27th October 2019) - Seth, Aradhna; Orkin, Sarah; Yodoshi, Toshifumi; Liu, Chunyan; Fei, Lin; Hardy, Jennifer; Trout, Andrew T.; Arce Clachar, Ana‐Catalina; Bramlage, Kristin; Xanthakos, Stavra; Mouzaki, Marialena
Summary: Background: Paediatric non‐alcoholic fatty liver disease (NAFLD) is highly prevalent among children with obesity. The primary objective of this study was determining whether obesity severity is associated with NAFLD severity. By using paediatric classifications for severe obesity, clinicians may be able to better risk stratify patients, which in turn would guide more effective management and treatment. Methods: Retrospective cohort study including patients followed at Cincinnati Children's Medical Center for NAFLD. Patients were categorized as overweight or class I, II, III obese based on established body mass index (BMI) cut‐offs. Liver disease severity was determined using biochemical, imaging (magnetic resonance elastography [MRE]), and histologic evidence of liver injury. Results: Three cohorts were studied individually based on the method used to assess disease severity (biochemical n = 767, imaging n = 366, and histology n = 249). Between the three cohorts, there were significant differences in age, proportion of patients with class II and class III obesity, and serum alanine transaminase (ALT) levels. In the biochemistry cohort, the odds of having ALT > 80 U/L were highest in patients with class III obesity ( P = .026). In the imaging cohort, liver stiffness was significantly different between BMI groups of patients ( P = .001). In the histology cohort, those with class III obesity had significantly higher odds of NAFLD activity score (NAS) ≥ 5 ( P = .012). Discussion: Obesity severity is associated with liver disease severity. Patients with more severe obesity are more likely to have more advanced liver disease, a finding that can assist in risk stratification, as well as monitoring and treatment approaches.